Life cycle assessment of roadworks in United Arab Emirates: Recycled construction waste, reclaimed asphalt pavement, warm-mix asphalt and blast furnace slag use against traditional approach. (1st June 2020) - Hasan, Umair; Whyte, Andrew; Al Jassmi, Hamad
Abstract: Life cycle assessment methodology was applied in this study to calculate environmental impacts of a 3.5-km-long dual carriageway asphalt highway section case study in Abu Dhabi across following life cycle stages: material extraction and production, material and equipment transport, construction, maintenance and rehabilitation; assuming a 30 years lifetime. Environmental impact assessment for air emissions and energy consumption generated by complete roadworks, namely: earthworks; pavement courses; concrete works for traffic barriers, kerbs, parapets, traffic signs, and light systems. A comprehensive analysis of environmental impact reduction was performed using recycled construction waste; reclaimed asphalt pavement; warm-mix asphalt with synthetic zeolite additives; and, slag as alternate material and production options. Actual field data for the road section using virgin materials and traditional asphalt production mix for pavement works and Portland cement concrete for the complete concrete works were used as the baseline case. Routine maintenance and periodic rehabilitation by milling and repaving wearing course (<4.5 cm depth) every 5 years was also analysed from an environmental impact reduction perspective. Environmental assessment considered all indicators from ReCiPe midpoint method. Results show that earthworks account for a significant portion (26% of CO2 eq.) of the environmental impacts for complete roadworks. The life cycle impact results of hot-mix asphalt and warm-mix asphalt were almost equal due to addition of synthetic zeolites. Results showed significant environmental impact reduction across all indicators, after coupling all alternate options as: 34% in CO2 eq.; 48% in energy consumption; 24.4% in NOx eq.; 21.53% in PM2.5 eq.; 21.2% in acidification; and, 10.4% in land use. Monte Carlo simulations confirm these results and the sensitivity of environmental benefits to the allocation methodology was also investigated, which showed that the results were only marginally sensitive to the allocation approach. This study noted higher environmental benefits than reported in roadworks literature due to alternate material and asphalt production options. Highlights: A comprehensive life cycle assessment for a UAE highway section by ReCiPe method. Employment of construction waste, RAP, warm-mix and GGBFS to reduce impacts. Earthworks and concrete works had a significant environmental burden in roadworks. Recycling and industrial by-products reduced impacts for concrete and earthworks. For asphalt courses, environmental benefits achieved by coupling warm-mix with RAP.